[2+2+2] Cycloisomerisation of Aromatic Cyanodiynes in the Synthesis of Pyridohelicenes and Their Analogues. Issue 40 (19th August 2016) - Klívar, Jiří; Jančařík, Andrej; Šaman, David; Pohl, Radek; Fiedler, Pavel; Bednárová, Lucie; Starý, Ivo; Stará, Irena G.
Abstract: We have developed a methodology for the synthesis of pyridohelicenes and their analogues based on the Ni 0 ‐, Co I ‐ or Rh I ‐mediated intramolecular [2+2+2] cycloisomerisation of cyanodiynes. It allows for folding the linear precursors into the corresponding helical backbones comprising the newly formed pyridine unit in their central part. Along with racemic pyrido[ n ]helicenes ( n =5, 6, 7) and their derivatives, both enantio‐ and diastereomerically pure pyrido[ n ]helicene‐like molecules ( n =5, 6) were prepared by employing the chiral substrate‐controlled cyclisation of the corresponding enantiopure cyanodiynes. Abstract : Helical structures : A methodology for the synthesis of various pyridohelicenes employing the Ni 0 ‐, Co I ‐, or Rh I ‐mediated intramolecular [2+2+2] cycloisomerisation of cyanodiynes was developed. Along with the racemic pyrido[ n ]helicenes ( n =5, 6, 7) and their derivatives, the enantio‐ and diastereomerically pure pyrido[ n ]helicene‐like molecules ( n =5, 6) were also prepared (see scheme).